Computational Investigation of the Ru‐Mediated Preparation of Benzothiazoles From N‐Arylthioureas: Elucidation of the Reaction Mechanism and the Origin of Differing Substrate Reactivity - Pacharaporn Krawmanee; M. Paul Gleeson; Duangkamol Gleeson (International Journal of Quantum Chemistry, 2024)
ABSTRACT Synthesis of novel benzothiazoles via intramolecular CS bond formation reactions is increasingly being explored since they have been found in a wide range of natural products and pharmaceutical agents. Sharma et al. reported the ruthenium‐catalyzed preparation of novel benzothiazole derivatives from N ‐arylthiourea precursors, with a range of reaction yields and selectivity being observed. We have employed a density functional theory‐based computational model to investigate the reaction mechanism leading to the benzothiazole product and help uncover the origin of the differing experimental yields and substrate specificities. We proposed a modified mechanistic scheme where the rate‐determining step to be the synchronized breaking of the peroxide bond of the oxidizing agent with the concomitant proton‐coupled electron transfer from the haloarene urea and a Ru‐bound water molecule, not electrophilic RuC bond activation. Evidence for this being the rate‐determining step is (a) the barrier is consistent with a lack of kinetic isotope effects associated with the ortho ‐H atom and (b) the computed rate‐determining barriers for 10 N ‐arylthiourea substrates show good correlation with the observed yield.
Keywords: Catalytic C–H Functionalization Methods; Sulfur-Based Synthesis Techniques; Cyclopropane Reaction Mechanisms